Alcohol industry influence on UK alcohol policy: A new research agenda for public health - Hawkins, Benjamin (Taylor & Francis, 2012)
The British government has been criticised for according industry interests too much weight in alcohol policy-making. Consequently, it has been argued that alcohol strategy in the UK is built around policies for which the evidence base is weak. This has clear implications for public health. The purpose of this commentary is to map recent developments in UK alcohol policy and related debates within the alcohol policy literature, thus laying the foundations for a systematic examination of the influence of the alcohol industry on alcohol policy. It highlights the changing structure of the industry and summarises what is known about the positions and strategies of industry actors towards alcohol policy. In so doing, it aims to contribute not just to debates about alcohol policy, but to a broader understanding of health policy processes and the relationships between government and other stakeholders. It advances a new research agenda focused on the role of corporate actors in the field of alcohol policy and public health more broadly.